PERAN KEPALA SEKOLAH DALAM PENGELOLAAN SARANA DAN PRASARANA DI SMP DARUL FALAH BANDAR LAMPUNG: MANAJEMEN SARANA PRASARANA - Afifah; Hadiati, Eti; Rochmatul Wachidah, Nor (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the role of the principal in managing educational facilities and infrastructure at SMP Darul Falah Bandar Lampung, as well as to identify the obstacles encountered in the process. The research employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The study focuses on seven aspects: the principal's role in planning, procurement, inventory, storage, maintenance, disposal, and supervision of facilities and infrastructure. The results show that the principal plays a strategic role as a planner, motivator, and supervisor in the management of school facilities, although there are still challenges such as limited budget and inadequate infrastructure. Therefore, the principal’s leadership plays a crucial role in creating an effective learning environment and in supporting the improvement of educational quality at the school.